2005
DOI: 10.1101/gr.3826505
|View full text |Cite
|
Sign up to set email alerts
|

Random mutagenesis of proximal mouse chromosome 5 uncovers predominantly embryonic lethal mutations

Abstract: A region-specific ENU mutagenesis screen was conducted to elucidate the functional content of proximal mouse Chr 5. We used the visibly marked, recessive, lethal inversion Rump White (Rw) as a balancer in a three-generation breeding scheme to identify recessive mutations within the ∼50 megabases spanned by Rw. A total of 1003 pedigrees were produced, representing the largest inversion screen performed in mice. Test-class animals, homozygous for the ENU-mutagenized proximal Chr 5 and visibly distinguishable fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 45 publications
4
66
0
Order By: Relevance
“…Phenotype analysis: The L5Jcs1 mutation was maintained in trans to the Rump white (Rw) inversion (for details see Wilson et al 2005). Homozygous embryos or neonates were obtained from intercrossing Rw/L5Jcs1 mice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenotype analysis: The L5Jcs1 mutation was maintained in trans to the Rump white (Rw) inversion (for details see Wilson et al 2005). Homozygous embryos or neonates were obtained from intercrossing Rw/L5Jcs1 mice.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a region-specific ENU mutagenesis screen directed at proximal mouse chromosome 5 yielded 37 embryonic lethal mutations (Wilson et al 2005). Here, we describe the characterization and positional cloning of one of these ENU-induced perinatal lethal mutations (L5Jcs1) that causes a homeotic transformation of the axial skeleton similar to that in Hoxc8 knockout mice (Le Mouellic et al 1992).…”
mentioning
confidence: 99%
“…Sperm dysfunction has been identified as one of the major factors in male infertility (Hull et al, 1985). Wilson et al (2005) mutagenized the mouse genome with N-ethyl-N-nitrosourea and found that males homozygous for the Ste5Jcs1 mutation were prone to low sperm motility. Subsequently, Harris et al (2007) mapped and cloned the Ste5Jcs1 mutation and identified a candidate gene for Ste5Jcs1 called Nsun7, which has a role in sperm motility.…”
Section: Discussionmentioning
confidence: 99%
“…More recent large-scale screens have not uncovered multiple allele of single genes as the 1/700 rate would predict (Kile et al, 2003). It has been estimated that the average mutation rate is likely to be half the rate seen in the specific locus test, on the order of one mutation per locus in 1,500 F1 progeny (Wilson et al, 2005). Knowing there are ϳ30,000 mouse genes, each F1 animal in a forward genetic screen is heterozygous for ϳ20 gene-inactivating mutations, so that even a small-scale screen can scan a meaningful number of functional mutations; for example, a screen of 150 lines would sample ϳ10% of the genome.…”
Section: Mutants and More Mutantsmentioning
confidence: 99%